Efikasi Efikasi Diri Pembatasan Cairan Terhadap Intradialytic Weight Gain Pasien Gagal Ginjal Kronik di Ruang Hemodialisa RSUD Pasar Minggu - Ni Putu Priska; Santi Herlina (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2019)
The common problems experienced by patients undergoing hemodialysis related to their non adherence againts the intake of fluids. Non adherence of patients with renal failure can causes excess volume of fluid in the body. To monitoring the success management of fluids intake can be measured by the Intradialytic Weight Gain (IDWG). IDWG was influenced by several factors, one of which factors is self-efficacy. The research’s aim is to know the relationship between self-efficacy’s fluid restriction with IDWG on chronic renal failure patients undergoing hemodialysis at RSUD Pasar Minggu. This research use analytic survey design with Cross Sectional approach. Self-efficacy’s fluid restriction measured by using questionnaires, whereas IDWG observed during pre and post hemodialysis accordinng to patient’s schedule. Of 40 respondents undergoing hemodialysis in RSUD Pasar Minggu, 20 patients have high self-efficacy and 20 other patients have low self-efficacy. While the averange of IDWG on patients is 2,188 Kg. The satistical test using Mann Whitney test shows that there is a relationship between self-efficacy’s fluid restriction and IDWG (p value = 0,001, α = 0,05). Thus, self-efficacy can affect IDWG.